Optimizing Energy Efficiency in Battery-powered IoT Devices through Hardware Optimization and Voltage Scaling - Bhavya, A. R.; Sudharshan, K. M. (Engineering, Technology & Applied Science Research, 2025)
With the rapid proliferation of battery-powered Internet of Things (IoT) devices, optimizing energy efficiency has become a critical challenge, especially in wireless communication modules. This work focuses on the power consumption analysis of the ESP32-WROOM module, a widely used wireless communication component in IoT applications. By evaluating five key interfaces, UART, I2C, SPI, I2S, and Wi-Fi, over different CPU clock frequencies (40 MHz, 80 MHz, 160 MHz, 240 MHz) and operating voltages (3 V and 3.3 V), this study provides a comprehensive understanding of how these parameters affect the energy efficiency in battery-powered IoT systems. The primary contribution of this work is the identification of critical trade-offs between clock frequency, voltage scaling, and power consumption across different interfaces. The findings reveal that higher CPU frequencies lead to increased power consumption across all interfaces, with I2S consuming the highest current (up to 64.6 mA) at 240 MHz and 3.3 V. Wi-Fi, often considered a power-intensive interface, showed significant current surges, particularly during connection establishment, with a peak current of 280 mA at 240 MHz and 3 V. These variations highlight the importance of effective voltage regulation during link establishment to mitigate power inefficiencies. Additionally, the voltage differential between 3 V and 3.3 V was found to influence overall power consumption, although certain interfaces at higher frequencies demonstrated marginal efficiency improvements when operating at 3.3 V. This highlights that while voltage selection is important, clock frequency adjustments have a more profound effect on power consumption. This work provides actionable insights for developers aiming to optimize power consumption in IoT applications. The findings provide guidance for selecting appropriate operating frequencies and voltage levels, contributing to significant energy savings and extended battery life in energy-constrained IoT and embedded systems.